Investigation of the Impact of Wellbore Trajectory on the Onset of Liquid Loading - Kinate, Bright; Epelle, Somiari (Journal of Earth Energy Science, Engineering, and Technology, 2024)
Liquid loading phenomenon and the influencing factors requires adequate investigation to avoid it and continue production without dropout. It is important to accurately predict liquid loading at an early stage and also when and where it starts to occur in the well in order to put together a suitable solution to combat it. In this work, the impact of wellbore trajectory on the onset of liquid loading in gas wells was investigated. Numerical simulation approach was adopted with two case scenarios of a wellbore model, “trajectory_1” inclined at 45.33° and a second wellbore model “trajectory_2” inclined at 46.39° were created and simulated for the different trajectories. At the start of production, the gas production rate was 0.703794MMscf/day for well with trajectory_1 and 0.703819 MMscf/day for well with trajectory_2. Result shows that for a period of 24hrs, the liquid production rate from well with trajectory_1 was lower than that from well with trajectory_2. Also, the liquid holdup of the well with trajectory_1 was higher than the well with trajectory_2 over a duration of 9.6hrs. A high wellbore inclined angle increased the liquid production rate and results in a reduction in liquid loading.